Clinical Management in Psychodermatology - Harth, Wolfgang; Gieler, Uwe.; Tausk, Francisco A.; Kusnir, Daniel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Psychocutaneous Medicine offers an overview of diseases in psychosomatic dermatology and creates a bridge between cutaneous and emotional disorders using extraordinary illustrations and clinical images of psychosomatic dermatology. It covers both common and rare diseases and helps doctors and psychologists recognize and deal with psychosocial features in dermatology and venerology. This superbly illustrated clinical atlas with concise text passages follows the American diagnosis classification DSM-V and current evidence-based guidelines. It allows rapid recognition of masked emotional disorders and thus administration of the most effective and efficient treatment as early as possible. Hone your diagnostic vision for psychosomatic disorders. Treat your patients efficiently and effectively. Psychocutaneous Medicine is a picture atlas and textbook that is indispensable for dermatologists, psychologists, pediatricians and general practitioners.
General -- Prevalence of Somatic and Emotional Disorders -- Specific Patterns of Disease -- Primarily Psychogenic Dermatoses -- Multifactorial Cutaneous Diseases -- Secondary Emotional Disorders and Comorbidities -- Special Focal Points in Dermatology -- Allergology -- Andrology -- Cosmetic Medicine -- Psychosomatic Dermatology in Emergency Medicine -- Surgical and Oncological Dermatology -- Photodermatology -- Suicide in Dermatology -- Traumatization: Sexual Abuse -- Special Psychosomatic Concepts in Dermatology -- From the Practice for the Practice -- Psychosomatic Psychodermatologic Primary Care and Psychosomatic Diagnostic -- Psychotherapy -- Psychopharmacological Therapy in Dermatology -- SAD Light Therapy, Vagal Stimulation, and Magnetic Stimulation -- The Difficult or Impossible-To-Treat Problem Patient -- The Dermatologist$1 (Bs Personal Challenges Within the Institutional Framework: Developing the Psychodermatologic Practice -- Liaison Consultancy -- New Management in Psychosomatic Dermatology -- A Look into the Future.s
Keywords: Medicine; Dermatology; General practice (Medicine).; Pediatrics; Psychology; Medicine & Public Health; Dermatology; Psychology, general; Pediatrics; General Practice / Family Medicine; Electronic books